An Efficient Agrobacterium-mediated Transformation Method for Sugarcane (Saccharum officinarum L.) - . Efendi; M. Matsuoka (Syiah Kuala University, 2011)
Investigation of transformation method for sugarcane was carried out by using Agrobacterium tumefaciens with a vectors pMLH7133 that contained CaMV35S promoter and marker genes. Embryogenic callus and cell aggregates of suspension culture were used as the target materials for transformation. The aggregates cell was sonicated, and co-cultured with Agrobacterium tumefaciens. The cells were cultured in N6-2 medium containing an appropriate antibiotic to eliminate bacterial contamination. Embryogenic callus was co-cultured with Agrobacterium, and was also cultured in N6-2 medium as same as suspension culture. Selection was carried out by culturing the treated suspension culture and embryogenic callus with MS medium containing geneticin. The transformed calli were transferred to MS-R9s for shoot formation. The transformed cells were analyzed for the distribution of GUS activity histochemically. After histohemical staining with X-glux, light microscopy observation revealed that the transformed calli derived from the NiF4, Ni9, and NCo310 cultivars had blue coloration in its tissue. Thus, the gene for GUS appeared to have been transferred and to be expressed in the calli. The construct of pCL4 was also integrated in the bacteria. Transient expression of GUS gene was successfully confirmed in the transformed Agrobacterium. When we use suspension culture, the proportion of the calli showing transient GUS expression was 4.7-fold greater with the vector in pMLH7133. We also successfully produced transformed calli with higher level of transient GUS expression. The percentage of the calli showing the best transient GUS expression is pCL4. The embryogenic callus was more competent for transfer of T-DNA into sugarcane cells. Analysis of GUS activity indicated that the gene was expressed into the calli of sugarcane. The Results indicate that the promoter can serve as an effective regulatory element to produce strong expression in callus of sugarcane. When we inoculated embryogenic callus with Agrobacterium harbored binary vector pCL4, we also successfully produced transformed calli with higher level of transient GUS expression. Thus, the gene for GUS appeared to have been transferred and to be expressed into the calli. Putative transformed plants were tested by performing PCR and Southern Hybridization to confirm the integration and expression of the introduced genes.